2012
DOI: 10.1111/j.1365-2982.2012.01953.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of, and predictors of, bile acid malabsorption in outpatients with chronic diarrhea

Abstract: Background  Many physicians do not consider the diagnosis of bile acid malabsorption in patients with chronic diarrhea, or do not have access to testing. We examined yield of 23‐seleno‐25‐homo‐tauro‐cholic acid (SeHCAT) scanning in chronic diarrhea patients, and attempted to identify predictors of a positive test. Methods  Consecutive patients with chronic diarrhea undergoing SeHCAT scan over a 7‐year period were identified retrospectively. Bile acid malabsorption was defined as present at a retention of <15%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 26 publications
8
73
0
5
Order By: Relevance
“…Furthermore, one-in-three CD patients had undergone intestinal resection previously and, given that bile acid diarrhea or small intestinal bacterial overgrowth may occur as a result of surgery, 10,11 and that there is overlap between the symptoms of these conditions and those of IBS, 12,13 it is possible that we have overestimated the prevalence of IBS. In addition, gold-standard investigations for IBD activity, including small bowel imaging and ileocolonoscopy were not performed routinely as the study was conducted within usual clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one-in-three CD patients had undergone intestinal resection previously and, given that bile acid diarrhea or small intestinal bacterial overgrowth may occur as a result of surgery, 10,11 and that there is overlap between the symptoms of these conditions and those of IBS, 12,13 it is possible that we have overestimated the prevalence of IBS. In addition, gold-standard investigations for IBD activity, including small bowel imaging and ileocolonoscopy were not performed routinely as the study was conducted within usual clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, interest in the potential for a missed organic GI diagnosis in patients with suspected IBS has increased. Previous studies have suggested that symptoms compatible with IBS may co-exist in patients with several organic GI diseases, such as inflammatory bowel disease, coeliac disease, or bile acid diarrhea, [15][16][17] and that some patients who meet criteria for IBS may have one of these underlying organic diseases. [18][19][20][21] Microscopic colitis (MC) consists of two primary subtypes: collagenous and lymphocytic colitis.…”
Section: Introductionmentioning
confidence: 99%
“…7 Individuals with IBS are more likely to consume health care resources than healthy individuals, 8 with up to 80% of sufferers consulting their primary care physician as a result of symptoms. 9,10 Diagnosing IBS can be challenging due to overlap between the symptoms that sufferers report and those of organic GI conditions such as celiac disease, [11][12][13] small intestinal bacterial overgrowth, 14 bile acid diarrhea, 15,16 exocrine pancreatic insufficiency, 17 or inflammatory bowel disease. 18 Partly as a result of this uncertainty, symptom-based diagnostic criteria were developed for use by physicians consulting with patients with suspected IBS as early as the 1970s, with Manning et al reporting six symptoms that were commoner among individuals found ultimately to have IBS after investigation.…”
Section: Introductionmentioning
confidence: 99%